Will I fit? The impact of social and identity determinants on teamwork in engineering education - Earle, Shayna; McDonald, Madison; Bengizi, Esra; Jones, Kim S. (Frontiers in Education, 2024)
In engineering as with many STEM spaces, the environment delivers many cues that affect psychological fit, which affects choices students make. Teamwork experiences can be particularly challenging for equity-deserving students. Using focus groups at a medium-sized multi-cultural Canadian university, we examined how engineering students navigated and experienced teamwork and how that interacted with social determinants (e.g. money and time constraints) and identity, including gender, race and sexuality. We used the framework of State Authenticity as Fit to Environment to develop themes of teamwork choices, experiences and outcomes. Social fit (respect from peers) and self-concept fit (whether self-image matches stereotype) affected many choices and experiences including selection of teammates with similar identities or allies. Women and low socio-economic status students sought self-concept fit by avoiding coding within teams. Visibly under-represented students felt pressure to excel to validate self-concept fit. The team environment itself sent messages about social and self-concept fit to many students, though the focus on collaboration and applications with social benefits often aligned with goal fit. These fit-guided choices and threats to fit nudged many students away from engineering careers. Interventions to address factors that cause negative experiences for marginalized students include strategic group composition, supporting mentorship and affinity groups, rotating group roles, structured collaboration, inclusive teamwork training and increasing diversity.